Retrieval of tropospheric water vapour from airborne far-infrared measurements: a case study - Warwick,L; Brindley,H; Di,Roma A; Fox,S; Havemann,S; Murray,J; Oetjen,H; Price,H; Schüttemeyer,D; Sgheri,L; Tiddeman,D (Journal of Geophysical Research: Atmospheres, 2022)
We describe studies undertaken in support of the Far-infrared Outgoing Radiation Understanding and Monitoring (FORUM) mission, ESA’s ninth Earth Explorer, designed to investigate whether airborne observations of far-infrared radiances can provide beneficial information on mid and upper tropospheric water vapour concentrations.Initially we perform a joint temperature and water vapour retrieval and show that the water vapour retrieval exploiting far-infrared measurements from the Tropospheric Airborne Fourier Transform Spectrometer (TAFTS) shows improvement over the a-priori Unified Model global forecast when compared to in situ dropsonde measurements. For this case the improvement is particularly noticeable in the mid-upper troposphere. Equivalent retrievals using mid-infrared radiances measured by the Airborne Research Interferometer Evaluation System (ARIES) show much reduced performance, with the degrees of freedom for signal (DFS), reduced by a factor of almost 2. Further sensitivity studies show that this advantage is decreased, but still present when the spectral resolution of the TAFTS measurements is reduced to match that of ARIES.The beneficial role of the far infrared for this case is further confirmed by performing water vapour only retrievals using ARIES and TAFTS individually, and then in combination. We find that the combined retrieval has a DFS value of 6.7 for water vapour, marginally larger than that obtained for the TAFTS retrieval and almost twice as large as that obtained for ARIES.These results provide observational support of theoretical studies highlighting the potential improvement that far-infrared observations could bring for the retrieval of tropospheric water vapour.